Optimization techniques for speedup in a parallel algorithm - Faria, Fairuz; Obin, Tahmid Tahsan; Rahat, Shah Md. Nasir; Chowdhury, Tanzim Islam (BRAC University, 2018)
Cataloged from PDF version of thesis report.